Math Calculators, Lessons and Formulas

It is time to solve your math problem

You are here:

# Calculators :: Analytic Geometry :: Parallel and Perpendicular Line

This calculator find and plot equations of parallel and perpendicular to the given line and passes through given point. The calculator will generate a step-by-step explanation on how to obtain the result.

## Parallel and Perpendicular Line calculator

Enter line in general form: ( Ax + By + C = 0 )
You can enter either integers (10), decimal numbers(10.12) or FRACTIONS (10/3). Important: The form will NOT let you enter wrong characters (like *, (, ), x, p,...) How to input??

0 1 2 3 4 5 6 7 8 9 - / . del
 Parallel line through the given point Perpendicular line through the given point
Show me an explanation.

## How to find line through a point parallel to a given line ?

Equation of the line that passes through the point $A(x_0, y_0)$ and is parallel to the line $y = mx + b$ is:

$${\color{blue}{ y - y_0 = m(x-x_0) }}$$

Example:

Find the equation of the line that passes through the point $A(-1, 2)$ and is parallel to the line $y = 2x - 3$

Solution:

In this example we have: $x_0 = -1,~~ y_0 = 2,~~ m = 2$. So we have:

\begin{aligned} y - y_0 & = m(x-x_0) \\ y - 2 & = 2(x-(-1)) \\ y - 2 & = 2x + 2 \\ y & = 2x + 2 + 2 \\ {\color{blue}{ y }} & {\color{blue}{ = 2x + 4}} \end{aligned}

Note : If you want to solve this problem using above calculator, you need to rewrite line equation in general form ( $2x - y - 3 = 0$ )

## How to find line through a point perpendicular to a given line ??

Equation of the line that passes through the point $A(x_0, y_0)$ and is perpendicular to the line $y = mx + b$ is:

$${\color{blue}{ y - y_0 = -\frac{1}{m}(x-x_0) }}$$

Example:

Find the equation of the line that passes through the point $A(-1, 2)$ and is perpendicular to the line $y = 2x - 3$

Solution:

In this example we have: $x_0 = -1,~~ y_0 = 2,~~ m = 2$. So we have:

\begin{aligned} y - y_0 & = -\frac{1}{m}(x-x_0) \\ y - 2 & = -\frac{1}{2}(x-(-1)) \\ y - 2 & = -\frac{1}{2}(x + 1) \\ (y - 2)\cdot{\color{red}{2}} & = -\frac{1}{2}\cdot{\color{red}{2}}(x + 1) \\ 2(y - 2) & = -(x + 1)\\ 2y - 4 & = -x - 1\\ 2y & = -x + 3\\ {\color{blue}{ y }} & = {\color{blue}{-\frac{1}{2}x + \frac{3}{2} }} \end{aligned}

Note : If you want to solve this problem using above calculator, you need to rewrite line equation in general form ( $2x - y - 3 = 0$ )

Quick Calculator Search